La literatura fantástica de Bioy Casares según la tríada hombre-razón-destino propuesta por el crítico Bernardo Ruiz (Crítica) - López Díaz, Ricardo (2023)
This paper aims to propose an analysis of fifteen pieces created by the Argentine writer Adolfo Bioy Casares (1914-1999) based on a postulate pronounced in 1976 by the Mexican critic Bernardo Ruiz. This exercise of reflection allows us to confront the narrated self of La invención de Morel (1940) and Historias fantásticas (1972) in a centrifugal and centripetal movement that questions both the forces of reason and the demands of destiny. As main conclusions, we can highlight that, although the subject of the narrative is capable of confronting and questioning the meanings proposed by these two instances —reason and destiny—, a perpetual restructuring of that environment is constantly required to redefine, again and again, certain parameters of fantastic literature.